2004
DOI: 10.1023/b:reom.0000032115.22510.b5
|View full text |Cite
|
Sign up to set email alerts
|

Probability-Possibility Transformations, Triangular Fuzzy Sets, and Probabilistic Inequalities

Abstract: Abstract.A possibility measure can encode a family of probability measures. This fact is the basis for a transformation of a probability distribution into a possibility distribution that generalises the notion of best interval substitute to a probability distribution with prescribed confidence. This paper describes new properties of this transformation, by relating it with the well-known probability inequalities of Bienaymé-Chebychev and Camp-Meidel. The paper also provides a justification of symmetric triangu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
358
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 501 publications
(370 citation statements)
references
References 43 publications
4
358
0
8
Order By: Relevance
“…This constitutes another generalisation of probabilistic conditioning in the sense of equation (35). The conditional belief is then obtained by duality Bel(A || C) = 1 − P l(A || C).…”
Section: Conditioning For Belief Functions and Imprecise Probabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…This constitutes another generalisation of probabilistic conditioning in the sense of equation (35). The conditional belief is then obtained by duality Bel(A || C) = 1 − P l(A || C).…”
Section: Conditioning For Belief Functions and Imprecise Probabilitiesmentioning
confidence: 99%
“…The probability-possibility transforms can thus yield probabilistic inequalities. It has been shown that a symmetrical triangular possibility distribution with bounded support [a, b] is consistent with any unimodal symmetrical probability function having the same support, and contains the prediction intervals of all these probability measures (Dubois et al [35]). Moreover, it is the most specific one having these properties (it is consistent with the uniform density over [a, b]).…”
Section: From Subjective Probability To Possibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The α-cuts or α-levels of a fuzzy set U , denoted by U α , are the intervals determined by the set of values verifying U (x) ≥ α, for α ∈ [0, 1]. Two of the most typical shapes of fuzzy sets considered in the literature are trapezoidal and triangular, where the last one is a special case of the first one (see, for instance, [8,12]). …”
Section: Preliminariesmentioning
confidence: 99%
“…More recently Mauris et al [81] noticed that starting from any family of nested sets around some characteristic point (the mean, the median,...), the above equation yields a possibility measure dominating P . Well-known inequalities of probability theory, such as those of Chebyshev and Camp-Meidel, can also be viewed as possibilistic approximations of probability functions.…”
Section: Probability-possibility Transformationsmentioning
confidence: 99%